การใช้ยีสต์ควบคุมโรคพืช - Chanchaichaovivat, Arun (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2010)
Using of Yeast for Biological Control Arun Chanchaichaovivat รับบทความ: 15 มษายน 2553; ยอมรับตีพิมพ์: 12 พฤษภาคม 2553 บทคัดย่อ ยีสต์เป็นจุลินทรีย์ที่มีความสำคัญในด้านอุตสาหกรรม การแพทย์ เกษตรกรรม และ สิ่งแวดล้อม การใช้ยีสต์ในทางเกษตรกรรมรูปแบบหนึ่ง คือ การนำยีสต์มาใช้ควบคุมโรคพืช ซึ่งต้องคำนึงถึงภาวะแวดล้อมที่เหมาะสมในการควบคุมจุลินทรีย์โรคพืชโดยไม่แพร่กระจายไปเกิดโรคในพืชชนิดอื่น ๆ การใช้ยีสต์ควบคุมโรคพืชอาจใช้ร่วมกับจุลินทรีย์ต่างชนิดกันหรือปรับปรุงพันธุ์ยีสต์ให้ควบคุมโรคพืชได้ดีขึ้น นอกจากนี้การใช้ยีสต์ควบคุมโรคพืชยังเป็นการลดการใช้สารเคมีและยาปฏิชีวนะต่าง ๆ ที่นำมาใช้ในทางเกษตรกรรม คำสำคัญ: ยีสต์ โรคพืช การควบคุมโดยชีววิธี เกษตรกรรม การปรับปรุงพันธุ์ Abstract Yeast is an important microorganism that uses in industry, medicine, agriculture and environment. A method to use the yeast in agriculture is to control the plant diseases. The appropriate environment for using yeast to control plant pathogens, not disperse to induce other plant diseases has been concerned. The plant disease control may use with other microbes, and the yeast improvement for high efficiency to control plant disease is a method used to control plant diseases. In addition, the control of plant diseases using yeasts uses to reduce the chemical and antibiotics in agricultures. Keywords: yeast, plant disease, biological control, agriculture, strain improvement